A Comparison of the Effectiveness of Share Decision Making and Standard Education for Cardiac Catheterization: A Pilot Study (International Journal of Studies in Nursing, 2021)
Background: Cardiovascular diseases are the second leading cause of death in the top ten leading causes of death in 2018 in Taiwan, and coronary artery disease is one of the main causes. Aim: To compare whether there are differences in patient knowledge, anxiety, and satisfaction between the utilization of patient decision aid for cardiac catheterization and routine health education. Subject and methods: Between July 2020 and September 2020, subjects were recruited in the clinics of the Department of Cardiology in a Veterans hospital in northern Taiwan. An experimental design was used for the study. Subjects were divided into two different education tool groups by randomization table. Subjects filled out the questionnaires before and after the education. Result: The patient knowledge before and after education in the RC group was improved by 2.30 points, and SDM group increased by 1.50 points (p-value